2007
DOI: 10.1152/jn.00957.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Hypothermia on Early and Late Epileptiform Events After Severe Hypoxia in Preterm Fetal Sheep

Abstract: Bennet L, Dean JM, Wassink G, Gunn AJ. Differential effects of hypothermia on early and late epileptiform events after severe hypoxia in preterm fetal sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 54 publications
(34 reference statements)
8
64
0
1
Order By: Relevance
“…In this study, both total and Δ power showed a transient "recovery" from 7 to nearly 23 h after the 25-min occlusion. This confounding increase corresponded with the development of delayed seizures, similar to previous reports of this paradigm (17,19,20). Even after resolution of …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, both total and Δ power showed a transient "recovery" from 7 to nearly 23 h after the 25-min occlusion. This confounding increase corresponded with the development of delayed seizures, similar to previous reports of this paradigm (17,19,20). Even after resolution of …”
Section: Discussionsupporting
confidence: 90%
“…Total EEG power (µV 2 ) was calculated from the intensity spectra. Quantitative EEG measurements for each waveform were performed to quantify power in the Δ (0-3.9 Hz), θ (4-7.9 Hz), α (8-12.9 Hz), and β (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) bands. This involved calculating power spectra (by fast Fourier transform) of the EEG on sequential epochs, using a 10 s Hanning window to minimize spectral leakage.…”
Section: Recordingsmentioning
confidence: 99%
“…Further, the maximal frequency of EEG transients in the preterm sheep model preceded secondary failure of mitochondrial oxidative activity on continuous near-infrared spectroscopic monitoring, whereas overt seizures did not occur until after the onset of the secondary fall [28]. Consistent with the hypothesis for a causal role for these events in the early recovery phase, experimentally, neuroprotection with hypothermia was closely associated with suppression of these events but not of overt seizures [67 ].…”
Section: Timing Of Treatment Is Criticalmentioning
confidence: 54%
“…Researchers used a variety of animal models of ischemia anoxic encephalopathy (rats, sheep and pigs) and low temperature treatment to further confirm the inhibitory effect of hypothermia on seizures. The results showed that low temperature obviously reduced the incidence of epilepsy caused by ischemia anoxic encephalopathy [14][15][16]. In 2008, Corry et al [17] first reported the use of mild hypothermia treatment in patients with RSE and the results showed that hypothermia inhibited epileptic seizures.…”
Section: Historical Evolutionmentioning
confidence: 98%